Cartooning for a modern Egypt - Zdafee, Keren, (Arts and Archaeology of the Islamic World;, 2019)
The Egyptian caricature is generally studied as part of Egyptian mass culture, and mainly discussed in the context of Egypt's anti-colonial resistance to British foreign rule, as part of the forging of a "national style". In Cartooning for a Modern Egypt, Keren Zdafee foregrounds the role that Egypt's foreign-local entrepreneurs and caricaturists played in formulating and constructing the modern Egyptian caricature of the interwar years, that was designated for, and reflected, a colonial and cosmopolitan culture of a few. Keren Zdafee illustrates how Egyptian foreign-local caricaturists envisioned and evaluated the past, present, and future of Egyptian society, in the context of Cairo's colonial cosmopolitanism, by adopting a theoretical, semiotic, and historical approach.